Cardiac Arrhythmias 1995 Proceedings of the 4th International Workshop on Cardiac Arrhythmias (Venice, 6–8 October 1995) - Raviele, Antonio (Springer Milan, 1996)
The subject of cardiac arrhythmias is of practical relevance. Various arrhythmias are found in different clinical situations, such as premature complexes in healthy individuals, supraventricular tachyarrhythmias in patients with Wolff-Parkinson-White snydrome, atrioventricular block, and ventricular fibrillation in cardiopathic conditions, especially in patients with ischemic disease. Topics of major interest are discussed in this volume: malignant ventricular arrhythmias, sudden death, automatic implantable cardioverter defibrillators, syncope, current indications for pacing therapy, radiofrequency catheter ablation, flutter, and atrial fibrillation